2002
DOI: 10.1002/pat.166
|View full text |Cite
|
Sign up to set email alerts
|

Modification of porous suspension‐PVC particles by stabilizer‐free aqueous dispersion polymerization of absorbed acrylate monomers

Abstract: The present study describes modification of porous PVC particles by polymerization of a monomer/crosslinker/ peroxide solution absorbed within the PVC particles. The modifying crosslinked polymers include butyl acrylate (BA) crosslinked with ethylene glycol dimethacrylate (EGDMA) and ethylhexyl acrylate (EHA) crosslinked with EGDMA. The monomer solution is blended with the PVC particles by dry-blending. The monomer absorbed particles are then polymerized in a stabilizerfree aqueous dispersion-polymerization. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…9-10, respectively), as in typical immiscible polymer blends [24]. The T g peaks of PBA are at about -22 °C, and of PEHA -56 °C, similar to literature reports [9,[25][26][27]. The neat PVC has a distinct T g at 64 °C and a wide β relaxation transition from -78 to 10 °C, attributed to the hindered segmental rotation about its main-chain axis [8,27].…”
Section: Mechanical Propertiessupporting
confidence: 63%
See 1 more Smart Citation
“…9-10, respectively), as in typical immiscible polymer blends [24]. The T g peaks of PBA are at about -22 °C, and of PEHA -56 °C, similar to literature reports [9,[25][26][27]. The neat PVC has a distinct T g at 64 °C and a wide β relaxation transition from -78 to 10 °C, attributed to the hindered segmental rotation about its main-chain axis [8,27].…”
Section: Mechanical Propertiessupporting
confidence: 63%
“…The formation of semi-IPN is generally known to enable control of phase separation [7], promote compatibility between immiscible polymer pairs [7][8][9][10], and thus provide a method for generation of desired properties. 2 In the present study, a route for producing semi-IPNs based on PVC and polybutyl acrylate (PBA), or polyethylhexyl acrylate (PEHA), crosslinked with ethylene glycol dimethacrylate (EGDMA) is described.…”
Section: Introductionmentioning
confidence: 99%
“…The current study focuses on commercial porous suspension PVC particles, modified by a polymerization/crosslinking process 7, 8, 17, 18. These authors suggested a structural model schematically illustrated in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, absorption of styrene and methyl methacrylate monomers in porous polypropylene particles and polymerization to form PP/PS and PP/PMMA blends was investigated by Rätzsch et al (29,30). Shach-Caplan et al (31,32) used PVC porous particles to absorb styrene, methyl methacrylate and other acrylate monomers. Polymerization of the monomer/peroxide solution absorbed in the PVC particles took place at 70°CϪ80°C, in surfactant-free aqueous dispersions to create various PVC blends.…”
Section: Department Of Chemical Engineeringmentioning
confidence: 99%